KESENIAN PROPHETIK - Wawan Kardiyanto (Institut Seni Indonesia Surakarta, 2006)
Artistry is result of mind expression and human being kindness with all its process. Art represent someone soul expression. Result of the soul expression round into the part of human being culture. Artistic of identik with the beauty. Beauty of real of identik with truth. Both owning is same value that is eternity. real Eternity values ever flange to God Thereby artistry also a media and discourse to serve to God. Such Artistry of more precise mention for him is Artistry of Prophetik . Artistry of Prophetic is artistry bringing prophecy mission within reason religion teaching bringing devotion essence go to God. Artistry of Prophetic is not simply art to be is artistic of free value. Artistry of Prophetic very condition assess the infinite and hold highing it is high. Values Believing in god here is truth, kindliness, justice and beauty.Key Word Artistry,Â Prophetik